‘Raising righteous billionaires’: The prosperity gospel reconsidered - Obadare, Ebenezer (HTS Teologiese Studies / Theological Studies, 2016)
How should we think of development within an ideological format in which individual subjects are abstracted from the constraints and necessities of social policy and the political structure? Using this question as a spark, this article critically deconstructs the Pentecostal prosperity gospel in Africa. Two overlapping arguments are advanced. One is that, in atomising the individual, Pentecostal prosperity gospel discounts power relations and the political, effectively dislocating the individual believer from the social matrix within which his or her agency is forged. Secondly, it is suggested that this attitude towards both the individual and the state puts Pentecostalism firmly within the orbit of neoliberalism. This article leverages this affinity for an understanding of how neoliberal ideas and conceptions of wealth, accumulation and self-actualisation are embedded and reproduced in Pentecostalism. It concludes that, because, on the one hand, it has no lever – historical or philosophical – on which it might be grounded, and on the other hand, since it has developed no cogent political economy to speak of, prosperity gospel, nay Pentecostal spirituality, offers no realistic path out of the African economic crisis.
free